(untitled) (Global Journal of Science Frontier Research, 2018)
This study examined the men and women participation in rice processing activities in Kebbi and Sokoto States, Nigeria. The specific objectives were to among others: describe the socio-economic characteristics of the rice processors’; ascertain awareness of rice processing technologies among men and women processors; and identify the constraints affecting men and women in rice processing. Data were collected from one hundred and fifty two (152) beneficiaries of the Agricultural Transformation Agenda Support Pragram -1 (ATASP-1) in the Staple Crop Processing Zones of Kebbi-Sokoto, covering (8) LGAs in the two states, purposively selected. The data were analyzed using descriptive statistics. The result of the socio-economic characteristics revealed that the majority (55.3%) had no formal western education, most(57.8%) of the beneficiaries were males, and(42.2%) were females. Similarly, majority(48.1%) were within the age bracket of between 31-40 years of ageand have been in rice processing for between 10 –14years (41.5%). Awareness and ranking of rice processing technologies indicates, rice de-stoned machines, false bottom parboilers, and rice husking machine and polishers. Major constraints were: inadequate funds(48.7%),lack of processing skill centers (38.6%), and inadequate capacity building on processing (32.5%).ATASP-1 should initiate and sustain facilitation and linkages to credit sources so that women and youths can access start–up capital, provision of skill acquisition centers to increase women knowledge in rice value addition and fortification were recommended among others.